SMART SILICON SENSORS BASED ON VERTICAL HALL EFFECT DEVICES - Dimitrov, Konstantin; Roumenin, Chavdar (International Journal of Computing, 2014)
Future integrated systems will benefit significantly from the progress in batch manufactured silicon sensors and signal processing techniques. Silicon technologies make possible to produce sensing microdevices combining maximal sensitivity, high accuracy and minimal design complexity. Smart sensors on the base of Vertical vector Hall effect devices offer a number of advantages including reducing mass, volume and power consumption; greater redundancy of system functions and simpler architecture. In view of these characteristics, it can be expected that such smart sensors will be used extensively wide if an adequate solution is found to reduce the design cost and simplify the electrical interface. Consequently, cost effective microsystems including vector magnetic sensors, circuits and eventually actuators can be fabricated. This paper presents a new approach in the field of signal processing for magnetic field sensors based on vertical Hall elements. A design example is illustrated specific problems and solutions associated with data converters and signal-processing functions for smart sensors.